Analysis of Serum microRNA Profile by Solexa Sequencing in Women With Endometriosis. (October 2016) - Wang, Lei; Huang, Wei; Ren, Caiping; Zhao, Ming; Jiang, Xingjun; Fang, Xiaoling; Xia, Xiaomeng
Objective(s): The potential roles of serum microRNAs (miRNAs), as biomarkers, in noninvasive diagnosis of endometriosis have been reported by microarray analysis. However, microarray analysis cannot perform well in outcome accuracy and repeatability and is not suitable to be used for exploring new targets. Here, Solexa sequencing, a wide and precise method, was adopted to further analyze the serum miRNAs profile in endometriosis, which may offer more evidence to apply serum miRNAs as biomarkers in diagnosis of endometriosis. Materials and Methods: Serum samples were collected from 30 patients with minimal–mild endometriosis and 20 women without endometriosis as control. Expression of serum miRNAs was measured by Solexa sequencing and validated by quantitative real-time polymerase chain reaction (qPCR). Results: Solexa sequencing showed 93.63% clean readouts for all small RNAs in the serum of patients with endometriosis and controls. A total of 108 miRNAs were found to be differentially expressed in the serum of patients with endometriosis by deep sequencing, compared to controls. Among them, 98 miRNAs were significantly downregulated, while 10 miRNAs were significantly upregulated. Only 21 of 98 significantly downregulated miRNAs, and none of significantly upregulated miRNAs were reported in published literatures, which may be due to the differences in samples and analytical methods. The Solexa sequencing results were consequently validated by qPCR in additional samples. Some miRNAs were identified to be promising diagnostic markers of endometriosis. The functional annotation of target genes revealed by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses indicated that a majority of differential miRNAs might be involved in endometriosis. Conclusion: Circulating miRNAs may be useful as detection biomarkers for the early diagnosis of minimal–mild endometriosis.